Evaluating the Role of International Research Collaboration in Strengthening Global Food Security and Agricultural Innovation - Olamidotun Nurudeen Michael; Omodolapo Eunice Ogunsola (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Global food security remains one of the most pressing challenges of the twenty-first century, driven by population growth, climate change, supply chain disruptions, and declining agricultural productivity in vulnerable regions. International research collaboration (IRC) has emerged as a powerful mechanism for addressing these challenges through shared innovation, cross-border knowledge transfer, and resource pooling. This review examines the role of international collaboration in advancing agricultural innovation, enhancing food production systems, and promoting sustainable agricultural practices. It explores how global partnerships among research institutions, governments, and private sectors contribute to developing climate-resilient crops, precision agriculture technologies, and policy frameworks supporting equitable food distribution. The paper further assesses the impact of funding mechanisms, capacity-building initiatives, and digital platforms that facilitate transnational cooperation. Drawing from successful global case studies such as CGIAR, FAO-supported initiatives, and multi-country R&D consortia, this study highlights the transformative potential of international collaboration in addressing systemic barriers to food security. Finally, the paper identifies policy recommendations for strengthening collaborative research frameworks, emphasizing inclusivity, data sharing, and technology localization to ensure sustainable agricultural innovation in both developed and developing economies.